Analisis Komparatif Potensi Likuefaksi Menggunakan Metode Youd & Idriss dan Idriss & Boulanger Berdasarkan Data SPT - M Naufal Ramadhan Naufal; Bagas Aryaseta; Karina Meilawati Eka Putri; Miguel Felix Wijaya (Universitas Muhammadiyah Surabaya, 2026)
Indonesia is one of the countries with high levels of seismic activity because it lies at the junction of three major tectonic plates and along the Pacific Ring of Fire. These conditions make several regions, including the Special Region of Yogyakarta, vulnerable to earthquakes and their associated impacts, one of which is liquefaction. This study aims to analyze the potential for liquefaction in the Yogyakarta Toll Road Construction Project, Section 2, Package 2.1, Sleman, using the Youd & Idriss and Idriss & Boulanger methods based on Standard Penetration Test (SPT) data. The analysis was conducted at three borehole locations—BH-86, BH-89, and BH-93—selected because they have the highest groundwater levels, thereby representing the most critical conditions regarding the likelihood of liquefaction. Earthquake magnitude variations of 6, 6.3, and 7 were used in this study to evaluate the influence of magnitude on liquefaction potential at the study site. The analysis was conducted by calculating soil resistance parameters against liquefaction based on each method, then comparing the results for each borehole and earthquake magnitude variation. The analysis results indicate that an increase in earthquake magnitude leads to an increase in soil cyclic load and a decrease in the Safety Factor value, thereby increasing the potential for liquefaction. Soil layers located below the groundwater table exhibit higher vulnerability to liquefaction compared to those above it. A comparison of the results shows that both methods exhibit similar trends, namely that the potential for liquefaction increases as earthquake magnitude increases. However, the Idriss & Boulanger (2008) method generally yields lower Safety Factor values compared to the Youd & Idriss (2001) method, making it more conservative in evaluating liquefaction potential. Thus, this study demonstrates that variations in earthquake magnitude and differences in analytical methods influence the results of liquefaction potential evaluations at the study site.